Blastogeny in tabulate corals: case studies using X‐ray microtomography. (26th November 2012) - Zapalski, Mikołaj K.; Dohnalik, Marek
<x xml:space="preserve">Abstract</x> X‐ray microtomography (XMT) is a non‐invasive and non‐destructive method that has often been used to study fossils. It allows serial sections to be made as little as few micrometers apart; such a resolution is unachievable for classical serial sectioning; moreover, in contrast to the latter, the specimen is not destroyed. Microtomography can, however, be applied only in cases where differences in X‐ray absorption between the skeleton and its infilling are great. We show that this method may be also applied to tabulate corals. Case studies of blastogeny are based on Silurian (Aulopora, Favosites) and Devonian (Thamnopora) specimens from Poland. We show that the sequence of events in the blastogeny of Aulopora sp. is different from that of 'Aulopora serpens minor' from the Devonian of the Holy Cross Mountains and similar to auloporids from the Devonian of England. Blastogeny in Favosites is very similar to that known from the related genera Squameofavosites and Thamnopora. This suggests that members of the genus Aulopora may be more diversified within the genus (as presently understood) than genera within the Favositidae.